PELATIHAN GURU BK SMP DI BEKASI UNTUK MELAKUKAN BIMBINGAN KELOMPOK - Wirda Hanim; Karsih Karsih (LP4MK STKIP PGRI Lubuklinggau, 2020)
The obstacle that encountered is group counseling services that rarely carried out apart from the limited time of service, it is also because of the skills of the Counselor in Junior High School. This condition also become more difficult due to group guidance services during the pandemic. The target of this service is BK teachers in Bekasi. Therefore, this service was made to improve BK teacher’s ability in giving a group counseling service. Initially, this service was designed with an offline system (offline), but in the pandemic period, the service was changed to online system (online). The stages carried out are the same as according to the initial plan, namely assessment, workshop, practice and evaluation. From the results of the assessment up to this stage, 5 groups were produced using a combined model. One group consisting of 10 students from 2 schools except SMP 19 Jakarta which is homogeneous in one school. The students involved all came from grade 7. Based on the aspect of the process, the activities of the devotion went well. Based on the aspect of the results, the target of this service is achieved that BK teachers increase their skills to conduct group guidance, and there is a change in the condition of student empathy. Key Words: Guidance Group, Empathy, Improve, Teachers